المضاربة في المصارف الاسلامية الصومالية: دراسة وصفية ودورها كأداة في التمويل الاسلامي: Al Mudarabah in Somali Islamic Banks: A Descriptive Study and its Role as a Tool in Islamic Finance - Yasin Mohamed Said, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث في العقود الأخيرة، انتشرت المصارف الإسلامية على نطاق واسع في العالم الإسلامي وغيره. حيث يُعَدُّ التمويل الإسلامي أساسًا رئيسيًا للمؤسسات المالية الإسلامية، على الرغم من أنه لم يبلغ ذروته بعد، فإن مستوى تطبيقه يختلف من بلد لآخر بالنسبة للشمولية والأساليب القديمة والجديدة. وفي الصومال، تشهد المصارف الإسلامية نموًا متسارعًا وتلعب دورًا مهمًا في تمويل الاقتصاد المحلي وتعزيز التنمية المالية. ومع ذلك، تواجه هذه المصارف تحديات في توفير وتنفيذ بعض الأدوات التمويلية المتوافقة مع مبادئ الشريعة الإسلامية. وعلى هذا تركز هذه الورقة على دراسة أدوات التمويل الإسلامي في المصارف الإسلامية الصومالية، من خلال المضاربة التمويلية كأحد أدوات التمويل الرئيسية. كما تم جمع المواد العلمية من خلال استخدام المنهج النوعي واستخدام اسلوب الاستقراء والتحليل الوصفي لتصنيف المعلومات والوصول إلى نتائج واضحة. تشير نتائج البحث إلى أن المصارف الصومالية تعتمد بشكل كبير على المضاربة كأداة تمويلية ناجحة في تمويل المشاريع، حيث تلتزم بمبادئ توزيع الأرباح وعدم تحمُل العملاء بأية خسائر مالية في حالة فشل المشروع. وتوصي الدراسة زيادة الجهود في تعزيز الامتثال لمبادئ المال الإسلامي وتوجيه المزيد من الاستثمارات نحو الأنشطة المتوافقة مع الشريعة. ABSTRACT In recent decades, Islamic banks have spread widely in the Muslim world and elsewhere. Islamic finance is a major foundation for Islamic financial institutions, although it has not yet peaked, its level of application varies from country to country for inclusiveness and old and new styles. In Somalia, Islamic banks are witnessing rapid growth and play an important role in financing the local economy and promoting financial development. However, these banks face challenges in providing and implementing some Sharia-compliant financing instruments. Accordingly, this paper focusses on the study of Islamic finance tools in Somali Islamic banks, through financial speculation as one of the main financing instruments. Scientific materials were also collected through the use of a qualitative approach and the use of induction method and descriptive analysis to classify information and reach clear results. The results of the research indicate that Somali banks rely heavily on speculation as a successful financing tool in project financing, as they adhere to the principles of profit distribution and do not bear any financial losses in the event of a project failure. The study recommends increasing efforts in promoting compliance with the principles of Islamic finance and directing more investments towards Sharia-compliant activities.